2013
DOI: 10.1155/2013/183463
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Cure Reaction, Rheology, Volume Shrinkage and Thermomechanical Properties of Nano-TiO2 Filled Epoxy/DDS Composites

Abstract: The cure reaction, rheology, volume shrinkage, and thermomechanical behavior of epoxy-TiO 2 nanocomposites based on diglycidyl ether of bisphenol A cured with 4,4 -diaminodiphenylsulfone have been investigated. The FTIR results show that, at the initial curing stage, TiO 2 acts as a catalyst and facilitates the curing. The catalytic effect of TiO 2 was further confirmed by the decrease in maximum exothermal peak temperature (DSC results); however, it was also found that the addition of TiO 2 decreases the over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 56 publications
0
14
0
1
Order By: Relevance
“…us, the development of composite material with combination of polyester resin in epoxy binder with improved and specified parameters of thermophysical properties is an actual task of modern industry. e authors had shown the results of investigation of thermophysical properties of epoxy composites in the works [7][8][9][10]. e kinetics of the glass transition process, thermal expansion, and shrinkage were described and the thermal resistance (Martens) of materials was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…us, the development of composite material with combination of polyester resin in epoxy binder with improved and specified parameters of thermophysical properties is an actual task of modern industry. e authors had shown the results of investigation of thermophysical properties of epoxy composites in the works [7][8][9][10]. e kinetics of the glass transition process, thermal expansion, and shrinkage were described and the thermal resistance (Martens) of materials was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Agglomerated nanoparticles can act as a defect within the coating, reducing the corrosion protection properties of the polymeric matrix. [7][8] Surface modification of the nanoparticles can reduce their surface energy and increase the interaction between the nanoparticles and the polymer matrix, preventing detrimental agglomeration. Among the different techniques for surface modification of nanoparticles, surface functionalization by organosilanes is the most commonly used method.…”
Section: Introductionmentioning
confidence: 99%
“…4,4′-DDS as a hardener showed the most remarkable peaks at 1116 cm −1 and 1270 cm −1 , ascribed to the symmetric and asymmetric stretching of –SO 2 -, respectively. In addition to symmetric and asymmetric stretching of –SO 2 -, strong peaks at 1450–1600 cm −1 and 3200–3400 cm −1 correspond to the bending vibrations of –NH– and stretching of NH 2 - (symmetric and asymmetric) in DDS, respectively [ 31 , 32 ]. The FT-IR spectrum of unmodified silica particles also demonstrated clear peaks at 1075 cm −1 ,798 cm −1 and 470 cm −1 responsible for the asymmetric, symmetric as well as bending modes of SiO 2 along with peak at 3400 cm −1 , due to the –OH stretching of silanol groups [ 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%